Transformasi Pendekatan Pembelajaran IPS di era Revolusi Industri 4.0 - Torkis Dalimunte; Ahmad Tarmizi Hasibuan; Sri Rahma Yani Harahap; Siti Fitri Hasibuan (Institut Agama Islam Hidayatullah Batam, 2025)
The Industrial Revolution 4.0 has driven a paradigm shift in the world of education, including in Social Science (IPS) learning. Transformation of learning approaches is necessary to answer the challenges of the times that demand mastery of technology, adaptive abilities, creativity, and critical thinking skills. This article is a literature review that explores the transformation of the IPS learning approach in the context of the Industrial Revolution 4.0 era. The study results indicate that IPS learning needs to be oriented towards developing 21st-century competencies, emphasizing practical, contextual application and integration of character and social values. Learning must be designed interactively, collaboratively, and fun to foster curiosity, empathy, social sensitivity, and civic responsibility. This transformation requires synergy between schools, families, communities, and the government to create a holistic and adaptive educational ecosystem. Thus, IPS education can produce a generation that is not only academically superior but also has social advantages and strong character in facing the dynamics of the Industrial Revolution 4.0.